Students' informal strategy on calculating the volume of three-dimensional shapes in STEM learning project: Design bakpia carton - Ulil Albab, Irkham; Nursyahidah, Farida; Mulyaningrum, Eko Retno (Metaverse: Journal of Mathematics Teacher Professional Development Research, 2025)
The best mathematics learning is through an activity, as the philosophy of mathematics arises because of human activities. Even so, in practice, mathematics learning is almost always carried out in a mechanistic deductive manner, meaning that students are taught definitions, formulas, practice questions, and then applied questions from formulas. The mathematics given can be in the form of "ready-to-use" as if it is standard knowledge that must be in school. The bad impact is that many students understand mathematical concepts as rigid tools, cannot be used in different situations, and are even easy to forget. This article aims to describe how the learning design of flat-sided shapes in STEM learning projects, Bakpia container design, raises various student strategies in calculating the volume of flat-sided shapes with an understanding that is informal, flexible, and does not only focus on formulas, but also gains an understanding of volume. and a more complete surface area. A research technique, called design research, was used to create the design. The Gravemeijer model's design research was assessed in terms of a hypothetical learning trajectory on the volume 3D object in the preliminary design, Design experiment, and retrospective analysis. The study produced the theoretical design and useful tools based on the approach that promotes student learning and adds to instructional theory on the volume of flat side space. The results of this study indicate that students grow their understanding of calculating the volume and surface area of ​​geometric shapes through informal strategies such as filling in times layers